2016
DOI: 10.3390/molecules21091122
|View full text |Cite
|
Sign up to set email alerts
|

Keratin Protein-Catalyzed Nitroaldol (Henry) Reaction and Comparison with Other Biopolymers

Abstract: Abstract:Here we describe a preliminary investigation on the ability of natural keratin to catalyze the nitroaldol (Henry) reaction between aldehydes and nitroalkanes. Both aromatic and heteroaromatic aldehydes bearing strong or moderate electron-withdrawing groups were converted into the corresponding β-nitroalcohol products in both DMSO and in water in the presence of tetrabutylammonium bromide (TBAB) as a phase transfer catalyst. Negligible background reactions (i.e., negative control experiment in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our group and others have demonstrated that the nitroaldol (Henry) reaction can be mediated by different biopolymers and enzymes . In the case of Au@apoferritin scaffolds, the potential catalytic activity could in principle arise from exposed basic groups of the protein itself and/or Au nanoparticles confined inside the apoferritin cage acting as a nanoreactor .…”
Section: Resultsmentioning
confidence: 99%
“…Our group and others have demonstrated that the nitroaldol (Henry) reaction can be mediated by different biopolymers and enzymes . In the case of Au@apoferritin scaffolds, the potential catalytic activity could in principle arise from exposed basic groups of the protein itself and/or Au nanoparticles confined inside the apoferritin cage acting as a nanoreactor .…”
Section: Resultsmentioning
confidence: 99%
“…Wood ash biocatalyst [63], alginic acid [64,65], boric acid [66], tartaric acid [67,68], citric acid [69][70][71], pectin [72], oxalic acid [73][74][75], saccharin [46,76,77], wool and keratin deriving from wool fibers [78][79][80], feathers [81][82][83][84], silk [85,86], plant derivatives, lemon juice [87,88].…”
Section: Natural Materials and Foods As Catalystsmentioning
confidence: 99%
“…In a very detailed review [ 21 ], the first thing that catches the eye is that wool powder proved not only to be a valuable tool for catalysis itself, as a specific source of keratin, but also a complexing agent for metal compounds of relevance in catalysis. Offering some examples, we introduce an innovative work released in 2016 [ 22 ], which confers to wool powder the role of support for nitroaldol reactions. The idea is quite simple: keratin deriving from wool fibers (unfortunately no detailed treatments are reported), in the presence of a mixture of H 2 O/TBAB, can afford nitroaldol products in high yields ( Scheme 1 ), perfectly stackable with results obtained with other polymers and comparable with other previous experiments, which involve the use of DMSO as a solvent.…”
Section: Woolmentioning
confidence: 99%
“…Metals have contributed predominantly in the context of C-C bond formation [ 23 , 24 , 25 ] Hydrogenations and hydrations have also been thoroughly studied, [ 26 , 27 ] so intensively that it would be impossible to report them all in this review. Still, on this topic, the review mentioned above [ 22 ] comes to our rescue, proposing us a series of examples reported in the literature about new wool-mediated approaches. Due to the high content of cysteine, these fibres can efficiently complex transition metals, especially palladium.…”
Section: Woolmentioning
confidence: 99%